Chemical and Energetical Properties in Methane Fermentation of Morphological Parts of Corn with Different Variety Earliness Standard FAO (Agricultural Engineering, 2023)
In the last decades, the production of biomass biofuels for thermochemical conversion to replace fossil fuels has attracted increasing attention as it offers significant environmental benefits. A very common way to convert biomass to energy is methane fermentation. The importance of biogas as a source of energy is growing. The use of biomass to biogas production on a large, global scale may lead to controversial competition for arable land, water, and consequently, food. Therefore, only waste materials and agricultural by-products and residues should be used for biogas production. Corn stover is a good example of agricultural residues for biogas production. Therefore, the aim of these studies was to determine the influence of corn variety earliness FAO on the chemical compositions and energy value of morphological parts (fractions) of corn plants. The research material consisted of morphological parts of corn plants: stalks, leaves, husks, and cobs of selected corn cultivars, differing in terms of their FAO earliness: early (FAO 220), medium-early q(FAO 240) and late (FAO 300) varieties. The research included laboratory investigations, elemental analysis, methane fermentation and statistical analyses of results. Based on the results of the study, it was concluded that the FAO earliness of a corn variety had a significant impact on the elemental composition, ash content, biogas, and methane yield in the corn morphological fractions. The highest methane yield of 267.4 m3·Mg−1 TS was found for the cucurbit cover leaves of a variety with an FAO 240 earliness standard.